Analysis Of Hydroponic Vegetable Sales Trend (Case Study: Fris Fresh Market) - amanupunnjo, grasiela delfine; Dr. Ir. L. O. Kakisina, M,Si; W. B. Parera, SP, M.Si (International Journal of Technology and Education Research, 2023)
This study aims to determine the sales trend of selling hydroponic vegetables for 24 month, knowing the sales forecast of hydroponic vegetables, especially mustard greens and lettuce in 2024. The results show that sales of hydroponic vegetables, especially mustard greens and lettuce, have a fluctuating trend from 24 month well as forecasting results obtained for the sale of hydroponic vegetables, especially spoon mustard and lettuce in 2023. For hydroponic vegetable sales, especially for spoon mustard and lettuce in 2023, it has decreased or increased, where spoon mustard this year is 1,666 and lettuce this year is 2,487.